First Steps to Personal Money Management. BANK-ED I Personal Money Management Series - Butterfield, Sherri M.; E.T.S. & Associates, San Diego, CA.; BANK-ED, Inc., San Diego, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This unit provides methods, materials, and activities for teaching about money in grades 4-6. It is divided into three sections: money and barter; disciplines and responsibilities; and organization and recordkeeping. Each section includes notes to aid the teacher in preparing and presenting the material, pre/post tests, and a series of one-page reproducible sheets which contain information or activities for students. Topics covered in the sheets include: (1) history of barter and money; (2) facts, vocabulary, and quotes about money; (3) purpose of money as exchange for goods and services; (4) work as a means of getting money; (5) need for discipline and responsibility in making and managing money; (6) ways of hiding and holding on to money; (7) history and purpose of checking accounts; (8) how to open a checking account and write checks; and (9) tips and practice in checkbook recordkeeping. Activities are designed to teach mathematics and life skills associated with managing money. The unit can be taught separately or as a part of regular classroom units in other subjects. (DC)
Availability: BANK-ED, Inc., 1133 G Street, San Diego, CA 92101.
ERIC Note: For related documents, see SO 015 209-210. One oversized chart not included.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Daily Living Skills; Instructional Materials; Interdisciplinary Approach; Intermediate Grades; Learning Activities; Mathematics Skills; Monetary Systems; Money Management; Teaching Methods; Units of Study; Worksheets; Checking Accounts -- PF Project; Guides, Classroom -- Teacher